1991
DOI: 10.1038/ki.1991.253
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric study of glomerular slit diaphragms fixed by rapid-freezing and freeze-substitution

Abstract: The widths of slit diaphragms in rat glomeruli were quantitatively measured on electron micrographs obtained by the rapid-freezing and freeze-substitution (FS) fixation method and compared to those prepared by conventional chemical fixation procedures, such as tannic acid, glutaraldehyde and osmium tetroxide (TGO) or glutaraldehyde and osmium tetroxide (GO) fixation. When fixed by FS using 2% osmium tetroxide, glomerular slit diaphragms had widths of 33.8 +/- 3.6 nm, but when fixed by TGO or GO they had widths… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 7 publications
1
40
0
Order By: Relevance
“…Because these studies used the conventional thin-sectioning method requiring harsh chemical treatments in sample preparation, it has later been suggested that the zipper-looking structure might be due to an artifact. Since then, the podocytepodocyte junction has also been studied by several other electron microscopic methods (32,33). These studies have indicated that the width of this junction varies between 20 and 50 nm.…”
Section: Discussionmentioning
confidence: 99%
“…Because these studies used the conventional thin-sectioning method requiring harsh chemical treatments in sample preparation, it has later been suggested that the zipper-looking structure might be due to an artifact. Since then, the podocytepodocyte junction has also been studied by several other electron microscopic methods (32,33). These studies have indicated that the width of this junction varies between 20 and 50 nm.…”
Section: Discussionmentioning
confidence: 99%
“…The classification of true widths provides an UNBiased estimate of widths, since the probability of perpendicular sectioning is independent of the slit width. The absolute measures of the slit width vary with the tissue procurement [25]. In this investigation all of the biopsies were treated in the same way except that in the non-diabetic control group a different buffer was used and the biopsies were taken under anaesthesia after a period of ischaemia during the transplantation of the kidney.…”
Section: Discussionmentioning
confidence: 99%
“…The filtration slits have a constant width of ϳ30 -40 nm (133,374) and are bridged by the slit diaphragm. Based on transmission electron microscopy findings in chemically fixed, tannic acid-stained material, Rodewald and Karnovsky (374) have published a model of the substructure of the slit membrane.…”
Section: Structure Of Podocytesmentioning
confidence: 99%